Pressure-induced phase transition in Bi2Se3 at 3 GPa: electronic topological transition or not?. (16th February 2016) - Bera, Achintya; Pal, Koushik; Muthu, D V S; Waghmare, U V; Sood, A K
Abstract: In recent years, a low pressure transition around GPa exhibited by the -type 3D topological insulators is attributed to an electronic topological transition (ETT) for which there is no direct evidence either from theory or experiments. We address this phase transition and other transitions at higher pressure in bismuth selenide (Bi2 Se3 ) using Raman spectroscopy at pressure up to 26.2 GPa. We see clear Raman signatures of an isostructural phase transition at GPa followed by structural transitions at  ∼10 GPa and 16 GPa. First-principles calculations reveal anomalously sharp changes in the structural parameters like the internal angle of the rhombohedral unit cell with a minimum in the c/a ratio near GPa. While our calculations reveal the associated anomalies in vibrational frequencies and electronic bandgap, the calculated invariant and Dirac conical surface electronic structure remain unchanged, showing that there is no change in the electronic topology at the lowest pressure transition.